2020
DOI: 10.48550/arxiv.2012.03088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superradiant phase transition in complex networks

Andrei Yu. Bazhenov,
Dmitriy V. Tsarev,
Alexander P. Alodjants

Abstract: In this work we consider a superradiant phase transition problem for the Dicke-Ising model, which generalizes the Dicke and Ising models for annealed complex networks presuming spin-spin interaction. The model accounts the interaction between a spin (two-level) system and external classical (magnetic) and quantized (transverse) fields. We examine regular, random, and scale-free network structures characterized by the delta-function, random (Poisson), and power-law exponent (p(k) ∝ k −γ ) degree distributions, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In [920] the atomic motion is quantized taking into account quantum fluctuations. A simplification could be to consider the atoms as point-like fixed points, but spatially distributed in the cavity such that the coupling strength becomes g → g i with g i a random variable with the subscript i marking atom i [921,922]. It was found that this modification could lead to a series of new transitions between ground states with abrupt changes in their atom-field entanglement.…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…In [920] the atomic motion is quantized taking into account quantum fluctuations. A simplification could be to consider the atoms as point-like fixed points, but spatially distributed in the cavity such that the coupling strength becomes g → g i with g i a random variable with the subscript i marking atom i [921,922]. It was found that this modification could lead to a series of new transitions between ground states with abrupt changes in their atom-field entanglement.…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%